2020
DOI: 10.3390/en13205310
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae Oil Production Using Wastewater in Japan—Introducing Operational Cost Function for Sustainable Management of WWTP

Abstract: A comparative evaluation of economic efficiency was performed for native polyculture microalgae oil production in an oxidation ditch (OD) process wastewater treatment plant (WWTP). A cost function was developed for the process. The operational cost per 1 m3 of wastewater (w.w.) was 1.34 $/m3-w.w. in the existing scenario, 1.29 $/m3-w.w. in algal scenario A (no cost for CO2 and waste heat) and 1.36 $/m3-w.w. in algal scenario B (no cost for CO2). The conditions were set as follows: hydraulic retention time (HRT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A WTW-LCA that analyzed the impact of algal biodiversity on biofuel production showed that certain polycultures improved GHG and EROI by 16% and 20%, respectively, compared to the best monoculture [75]. It has also been suggested that in a 0.8 m depth polyculture of microalgae, based on 86% heat recovery in the HTL process previously reported, WTG-LCA of combining algae biomass/biocrude-oil production and wastewater treatment reduced the CO 2 emissions of the conventional wastewater treatment system by 33% [8]. Thus, the benefits for reduced CO 2 emission and increased net energy-gain are clearly demonstrated for the proposed biocrude oil production by HTL employing the polyculture system for wastewater treatment.…”
Section: Life-cycle Assessment (Lca) Of Microalgae-based Biofuel Productionmentioning
confidence: 92%
See 3 more Smart Citations
“…A WTW-LCA that analyzed the impact of algal biodiversity on biofuel production showed that certain polycultures improved GHG and EROI by 16% and 20%, respectively, compared to the best monoculture [75]. It has also been suggested that in a 0.8 m depth polyculture of microalgae, based on 86% heat recovery in the HTL process previously reported, WTG-LCA of combining algae biomass/biocrude-oil production and wastewater treatment reduced the CO 2 emissions of the conventional wastewater treatment system by 33% [8]. Thus, the benefits for reduced CO 2 emission and increased net energy-gain are clearly demonstrated for the proposed biocrude oil production by HTL employing the polyculture system for wastewater treatment.…”
Section: Life-cycle Assessment (Lca) Of Microalgae-based Biofuel Productionmentioning
confidence: 92%
“…This model suggests that algae fuel production is economically feasible combined with carbon credits that promote the realization of a low-carbon society. Ishizaki et al [8] suggested that a 0.8-m depth polyculture-based wastewater treatment had the same cost-effectiveness as the conventional wastewater treatment, even though the resulting biocrude oil was sold at the same price as fossil crude oil. Thus, further reduction of MFST can be expected by introducing a combination of algae and sewage treatment to the NERL model.…”
Section: Life-cycle Assessment (Lca) Of Microalgae-based Biofuel Productionmentioning
confidence: 99%
See 2 more Smart Citations